Zarządzanie wiedzą jako czynnik sukcesu rynkowego przedsiębiorstwa - Sudolska, Agata (Knowledge Management as a Factor of Enterprise Success on the Market, 2006)
Managing enterprise in the conditions of globalisation requires organizations characterised by continuous efforts to renew internally, forcing them to acquire new competences and learn continuously. Every enterprise striving to maintain its market position, to stay competitive on the global market, has to learn faster than its rivals.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1104, s. 211-218